Identification of Groundwater Potential Using the Schlumberger Configuration Resistivity Geoelectric Method - Jupri, Ahmad; Tahsya, Muhammad Abu; Rahayu, Rachmawati Noviana; Safata, Hendri Oky (Jurnal Biologi Tropis, 2024)
The availability of groundwater is an important factor in meeting the need for clean water for human populations and ecosystems. Groundwater utilization in the world continues to increase every year along with the increase in population. This study aims to identify groundwater potential using resistivity geoelectric method with Schlumberger configuration in Pujut District, Mertak village. This area is one of the areas that often experiences drought, especially during the dry season. The research was conducted by conducting field surveys using geoelectric devices and resistivity data analysis. This method utilizes the propagation properties of electric current flowed into the soil through two current electrodes, then the potential difference that occurs is measured through two potential electrodes plugged into the ground surface. Analysis of resistivity data yielded a picture of the potential distribution of groundwater in six sites.  The identified characteristics of subsoil are breccia, loam, limestone, alluvial, and sandstone. At locations 4,5 and 6 have aquifer layers with an average depth of 30 meters. This layer is dominated by a hard layer (sandstone) and a soft layer (limestone). This research provides a better understanding of the distribution and characteristics of aquifers in the Pujut area, especially Mertak village, so that the results of this research can be the basis for making decisions on groundwater resources management and further development in mapping groundwater resources in the region with other geological contexts.